Differences in the effect of maternal smoking during pregnancy for childhood overweight before and after 5 years of age. Issue 5 (4th April 2013) - Suzuki, Kohta; Sato, Miri; Ando, Daisuke; Kondo, Naoki; Yamagata, Zentaro
Abstract Aim This study aimed to clarify the association between maternal smoking during pregnancy and childhood overweight during different periods using two cohort studies from the same population: the birth cohort (the 1st cohort) and the non‐overweight children at 5 years of age cohort (the 2nd cohort) by sex. Material and Methods The study population comprised children born between 1 April 1991 and 31 March 1999 in Koshu City, Yamanashi Prefecture, Japan, and their mothers. The dependent variables were diagnosis of overweight in each cohort. The primary independent variable was maternal smoking during pregnancy. Multiple logistic regression models were applied for these statistical analyses. Results Mothers who answered the questionnaire during early pregnancy gave birth to a total of 1644 babies during the study period. The 1st cohort consisted of these babies and were followed until 5 years of age. The 2nd cohort consisted of 1131 children who were diagnosed as normal weight at 5 years of age and followed until 9–10 years of age. There was an association between maternal smoking during pregnancy and overweight only in boys in the 1st cohort analysis (adjusted odds ratio, 4.5; 95% confidence interval, 2.0–10.2). Conclusions These results suggest that the effects of maternal smoking during pregnancy on childhood overweight tend to appear before 5 years of age, especially in boys. It is necessary for children whose mother smoked during pregnancy, especially in boys, to be careful with their diet and physical activity in order to prevent childhood obesity.